Cele izolacji penitencjarnej w perspektywie odrzucenia idei przymusowej resocjalizacji - Kalisz, Tomasz; Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The aim of the paper is to present the purposes of carrying out the penalty of deprivation of liberty in the light of the current criminal codification. This issue is one of the most difficult discussion fields within the penitentiary law. The attempt to establish the aims of the penalty of deprivation of liberty on the realization stage primarily has arelevant practical meaning but the theoretical meaning is also important. Thorough assignments in this passage determine the way of interpretation of overall view of institutions that are connected to the content of the penalty of deprivation of liberty. These assignments point to the basic terms of reference of penitentiary administration. They are also one of the crucial indicators for the trends in penitentiary policy. The aims of carrying out the penalty of deprivation of liberty in the Executive Penal Code of 1997 were treated in aspecific way because they were specified in aseparate chapter of the Code entitled “The aims of the execution of penalty” Article 67 of the Executive Penal Code.
Keywords: izolacja penitencjarna; przymusowa resocjalizacja; resocjalizacja skazanych